Force, velocity, and power adaptations in response to a periodized plyometric training program - Petushek, E.; Garceau, L.; Ebben, W. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
This study assessed kinetic, kinematic and temporal adaptations to the countermovement jump in response to a 6 week periodized plyometric training program. Twenty recreationally active women were randomly assigned to a plyometric training or control group. Testing consisted of 3 maximal countermovement jumps on a force platform prior to and after the six weeks of training. A two-way repeated measures ANOVA was used to assess differences between pre- and post-testing sessions and between groups. Post-test eccentric and concentric velocity, power and jump height were significantly greater (p < 0.05) in the training group. Periodized plyometric training is effective for increasing jump height, and augmentations are likely due to enhanced eccentric velocity.